2022
DOI: 10.1186/s13071-022-05221-x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of ixodid ticks and tick-borne pathogens of domestic animals in Ethiopia: a systematic review

Abstract: Background In Ethiopia, ixodid ticks and associated tick-borne pathogens (TBPs) are of great importance from both a veterinary and public health point of view. This review aimed at compiling available published data on the distribution of ixodid tick species and TBPs in the country. Methods A standard review approach was employed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Published peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
(108 reference statements)
1
4
0
Order By: Relevance
“…A systematic review using 35 published articles showed about 19 tick species under the genus Amblyomma , Rhipicephalus (Boophilus ), Rhipicephalus , Hyalomma , and Haemaphysalis reported in various domestic animals in Ethiopia during the period of 2001 up to October 30, 2020. 24 Recently published articles from Gondar, Eastern Hararghe, and Selamago support the current and previous studies finding in Ethiopia, where Amblyomma is the predominant genus. 19,25,26 The overall prevalence of tick populations in the Selamago district was significantly ( P < .05) higher compared to non-infected ones.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…A systematic review using 35 published articles showed about 19 tick species under the genus Amblyomma , Rhipicephalus (Boophilus ), Rhipicephalus , Hyalomma , and Haemaphysalis reported in various domestic animals in Ethiopia during the period of 2001 up to October 30, 2020. 24 Recently published articles from Gondar, Eastern Hararghe, and Selamago support the current and previous studies finding in Ethiopia, where Amblyomma is the predominant genus. 19,25,26 The overall prevalence of tick populations in the Selamago district was significantly ( P < .05) higher compared to non-infected ones.…”
Section: Discussionsupporting
confidence: 75%
“…truncatum is generally found in arid parts of tropical Africa with annual rainfall ranging from 250 to 650 mm, where this ecology is more common in Selamago than in central Ethiopia. 24 The low incidence in Ethiopia’s central highlands may be due to considerable rainfall. 49…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CCHF, is a zoonotic arboviral disease that poses a great threat to public health therefore according to the World Health Organization (WHO), CCHFV is the most predominant causative agent of viral hemorrhagic fever outbreaks worldwide (Sorvillo et al 2020). Humans and a wide range of other animal species are at risk of contracting CCHFV (Ali et al 2019, Kaba 2022. It has been reported that CCHFV can be transmitted to humans through a tick bite, contact with blood, body fluids, or tissues of a viremic animal or human (Bente et al 2013).…”
Section: Introductionmentioning
confidence: 99%